The effects of maternal smartphone use on mother–child interaction. Issue 2 (22nd November 2021) - Lederer, Yael; Artzi, Hallel; Borodkin, Katy
Abstract: This study assessed the effects of maternal smartphone use on mother–child interaction. Thirty‐three Israeli mothers and their 24‐ to 36‐month‐old toddlers (16 boys) from middle‐high socioeconomic status participated in three within‐subjects experimental conditions: maternal smartphone use, maternal magazine reading, and uninterrupted dyadic free‐play. The mothers produced fewer utterances, provided fewer responses to child bids, missed child bids more often, and exchanged fewer conversational turns with their children when engaged with a smartphone or printed magazines compared to uninterrupted free‐play. The quality of maternal responsiveness was also decreased. These findings suggest maternal smartphone use compromises mother–child interaction, which given smartphone ubiquity in daily life may have negative effects on child development in various domains, including language, cognition, and socioemotional regulation.